The impact of the South African Renewable Energy Independent Power Producers Procurement Programme on South African communities: A case study - Sonday, Aamirah (Graduate School of Business (GSB), 2022)
South Africa is one of the most unequal societies in the world with vast differences in socioeconomic conditions. At the same time its carbon emissions are the highest on the continent. Recognising the need to both reduce poverty and inequality and carbon emissions, the South African government introduced the Renewable Energy Independent Power Producer Procurement Programme (REIPPPP). The REIPPPP is a competitive bidding scheme and once independent power producers (IPPs) are appointed as preferred bidders a nonnegotiable, standardised and rand (ZAR)-dominated 20-year power purchase agreement is signed with the national energy producer, Eskom. In order to qualify, project companies must commit to certain economic and socio-economic development criteria within their host communities. The inclusion of this requirement is meant to uplift the quality of life in the host communities. The objectives of this study included exploring the socio-economic benefits of the REIPPPP using the SlimSun Swartland Solar Park (SlimSun) project in the Swartland Municipality as a case study. This study was thus exploratory in nature and qualitative research techniques were used. The sample population was derived through convenience sampling and data was collected via interviews with the project company, a local NGO, the municipality and the local community trust. From the thematic analysis, community trust; education; food, nutrition and healthcare; and upliftment and dignity were identified as the socio-economic development benefits which the host community derived from the REIPPPP. In investigating the experience and perceptions of community members with SlimSun, a key theme that emerged was the importance of trust between stakeholders and how strong community relationships, including with local government, helps in identifying initiatives that address the needs of the community. While this study cannot make generalisations, based on the findings, the researcher would recommend that the REIPPPP Office considers providing guidelines to the REIPPPP projects that working with local governments and NGOs may help to create lasting benefits to host communities.